Drastic enhancement of carbon dioxide adsorption in fluoroalkyl-modified poly(allylamine). Issue 17 (21st April 2021) - Koutsianos, Athanasios; Hamdy, Louise B.; Yoo, Chun-Jae; Lee, Jason J.; Taddei, Marco; Urban-Klaehn, Jagoda M.; Dryzek, Jerzy; Jones, Christopher W.; Barron, Andrew R.; Andreoli, Enrico
Abstract : Aminopolymer functionalization with fluoroalkyl chains and resulting void volume afford 4.1-fold increase in amine efficiency and 2.8-fold increase in CO2 capture capacity in the fluorinated material. Abstract : Polyamine-based carbon dioxide sorbents suffer from a seesaw relationship between amine content and amine efficiency. High polyamine loadings equate to increased amine contents, but often at the expense of amine efficiency. Carbon dioxide mass transport in compact polymers is severely limited, especially at ambient temperature. High polymer contents curtail diffusion pathways, hindering CO2 from reaching and reacting with the numerous amine functions. Here, we overcome this issue using poly(allylamine) (PAA) grafted with short fluoroalkyl chains and then cross-linked with C60 . As experimentally evidenced by positron annihilation lifetime spectroscopy, the incorporation of fluoroalkyl chains generates free volume elements that act as additional diffusion pathways within the material. The inclusion of void volume in fluoroalkyl-functionalized PAA sorbents results in radically increased CO2 uptakes and amine efficiencies in diluted gas streams at room temperature, including simulated air. We speculate that the hydrophobic fluorinated functions interfere with the strong amine hydrogen bonding network disrupting and consequently altering the packing and conformation of the polymer chains. The evidence presented here is a blueprint for the development of more efficient amine-based CO2 sorbents.